Adopting DevOps Principles, Practices and Tools : Case: Identity & Access Management - Blomberg, Vilma (My University, 2019)
Adopting DevOps has been of interest for many organizations and practitioners for a while now due to its various benefits for business. However, there is a lack of knowledge and understanding on what is meant by DevOps when it comes to the key concepts, practices, tools, and the benefits and challenges of DevOps adoption. Organizations and teams are missing guidance on how to adopt DevOps in their specific context. This design science research is conducted to understand how to adopt DevOps principles, practices and tools in the Identity and Access Management of a large multinational corporation. The result of this study are the proposed models for adopting DevOps, including the formation of the teams and the processes covering build, test and deployment of identity management system (SailPoint IIQ) and onboarding new applications to the system. Three design artifacts are built and evaluated against identified problem areas in DevOps adoption, providing insights to the research community and industry practitioners.
Keywords: DevOps, IAM, Identity Management, Continuous Integration, Continuous Deployment, Contin-uous Feedback, Agile, SailPoint, automation, software development